Morphology and relative growth in Clypeaster europacificus (Clypeasteroida: Clypeasteridae) from the Gulf of California - Conejeros-Vargas, Carlos-Andrés (2021)
Introduction: Clypeaster europacificus is a species of sand dollar found from 0 to 200 m in the Gulf of California. Objective: Describe the morphology and relative growth in the test of C. europacificus. Methods: We measured 1 846 museum specimens of C. europacificus (N = 1 846) and analyzed growth pattern in 32 specimens from Baja California Sur, Mexico (64 m depth). We studied five variables: major radius (R) (independent variable), minor radius (r), length of anterior petal (LP), total test area (A) and dry weight (P). Results: The petaloid cover area and the outline of the test are the important taxonomic characters for C. europacificus: they range from almost round in small specimens (≤ 3 cm in radius) to wavy, emphasizing a pentagonal outline, in larger organisms (≥ 3.1 cm in radius). Conclusions: There is negative allometric growth in the relationships R vs. r, R vs. A, and R vs. P; while the relationship R vs. LP has positive allometric growth.